Development of Entrepreneurial Activity Using the Integration of Human Capital and Green Technologies to Optimize the Sustainable Development of the Territories - Alma Karshalova; Aidos Akpanov; Santay Tleubayeva; Anuar Belgibayev; Askar Makhmudov; Aigul Atchabarova; Margarita Zholayeva (Qubahan Academic Journal)
The development of the tourism sector faces serious challenges, which are related to its environmental transformation, digitalization, and integration of new technologies, as well as competitiveness. Tourists' behavior is also changing. The future demand for tourism is likely to be driven by growing environmental awareness, increased use of digital services and new technologies, a shift towards a more personalized travel experience, and ensuring well-being and better engagement with local communities and culture. Meeting the requirements of the modern tourism industry is a problem not only for the Republic of Kazakhstan but also for other countries that strive for sustainable development of the tourism sector. The purpose of the study is to identify ways to develop entrepreneurial activity by integrating human capital and green technologies to optimize the sustainable development of the tourism sector. The paper examines the basic theoretical concepts of the essence and forms of sustainable tourism and presents the concept of the integration of human capital and green technologies to achieve the principles of sustainable development. Based on an expert survey, strengths, weaknesses, opportunities, and threats analysis, and statistical methods, the main ways of promotion and development of sustainable tourism, as well as measures to integrate human capital and green technologies into entrepreneurial activities in the tourism sector in the East Kazakhstan Region, have been identified. The authors have concluded that the introduction of green technologies and the integration of human capital with them provide new standards for the quality of tourist services while preserving the natural resources of the region.